How to grow yams and bananas - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
Two useful booklets offer practical and easy-to-follow guidance on cultivating two key ACP crops yams and bananas.